Diagnosa Kesulitan Belajar Matematika Siswa Kelas V MI NW Pancor Kopong NTB - Muh. Yazid; Lale Aprihatin Diana Safitri; Saprudin Jauhari (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
This study wants to reveal the factors of low student achievement, especially in mathematics. The factors of learning difficulties experienced by students of class V MI NW Pancor Kopong. Learning difficulties experienced by students result in underachievement in these subjects. The study was conducted to determine the factors of learning difficulties experienced by fifth grade students of MI NW Pancor Kopong. This research is a qualitative descriptive study. The subject of the research was the fifth grade students who had difficulty learning, namely students who had KKM scores that did not meet the UAS. The data collected in the form of documentation data, and interviews. Data collection was carried out using questionnaires, documentation, and interviews. Data analysis to illustrate psychological factors of learning difficulties by calculating the percentage of questionnaire results in fifth grade students of MI NW Pancor Kopong. and Data analysis to determine the psychological factors of learning difficulties by recording the results of the interview.